Dietary supplementation of Ficus hookeri leaves as herbal feed additive affects nutrient utilization and growth performances in growing crossbred calves - SANTRA, A; TAKU, T; TRIPURA, S; DAS, S K; DUTTA, T K (The Indian Journal of Animal Sciences, 2023)
The objective of this study was to evaluate the effect of dietary supplementation of Da qing shu (Ficus hookeri) leaf meal as herbal feed additive on nutrients utilization and growth performance of growing crossbred calves. Ten Jersey male cross-bred calves (~ 4 months of age) were divided equally into two groups (G1 and G2) and were fed ad lib. under stall feeding on a paddy straw based mixed ration consisting of 50% paddy straw and 50% concentrate mixture for a duration of 140 days. Two types (C1 and C2) of iso-nitrogenous concentrate mixtures were prepared. Four per cent (w/w) wheat bran in concentrate mixture (C2) of test group (G2) was replaced by sun dried ground Ficus hookeri leaf meal. Experimental calves of test group (G2) were fed Ficus hookeri leaf meal @ 2% of the diet. Daily dry matter intake (g/d) was similar among the calves of two experimental groups. Apparent digestibility of DM, OM, NDF, ADF and cellulose improved in the Ficus hookeri leaf meal fed calves (G2). DCP value of the ration was similar while, TDN value of the ration was higher in the calves of Ficus hookeri leaf meal supplemented group (G2). However, plane of nutrition among the calves of both experimental groups was similar. Average finishing body weight, daily body weight gain, feed conversion efficiency and blood glucose level were higher in Ficus hookeri leaf fed calves (G2). Therefore, it may be concluded from the results of the study that dietary supplementation of Da qing shu (Ficus hookeri) leaf meal as herbal feed additive @ 2% of total mixed diet significantly improved the fibre digestibility, average daily body weight gain and feed conversion efficiency in growing Jersey male crossbred calves.